1999
DOI: 10.1192/pb.23.4.203
|View full text |Cite
|
Sign up to set email alerts
|

Experience and application of HoNOS65+

Abstract: Aims and methodThe implementation of the Health of the Nation Outcomes Scales for Old Age Psychiatry services (HoNOS66+) in a National Health Service trust is described. Some preliminary data are reported for illustrative purposes.ResultsLessons learnt from this process are identified, and further work needed both on the glossary for the scales and on systems for trapping data is suggested.Clinical implicationsThese remain uncertain. It may be that HoNOS65+ will remain a purely administrative tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 1 publication
0
12
1
Order By: Relevance
“…For the HoNOS65þ the results were more variable. When 50 professionals rated a video of a patient there was 'difficulty achieving acceptable inter-rater reliability' for items 10, 11 and 12 (Allen et al, 1999). It could be argued that these are very difficult areas to assess using such an indirect method.…”
Section: Inter-rater Reliabilitymentioning
confidence: 94%
See 3 more Smart Citations
“…For the HoNOS65þ the results were more variable. When 50 professionals rated a video of a patient there was 'difficulty achieving acceptable inter-rater reliability' for items 10, 11 and 12 (Allen et al, 1999). It could be argued that these are very difficult areas to assess using such an indirect method.…”
Section: Inter-rater Reliabilitymentioning
confidence: 94%
“…In a study of the HoNOS65þ in clinical practice (Macdonald, 2002), there was a demonstrated discrepancy between raters, which Macdonald (Allen et al, 1999) Pilot study implementing HoNOS65þ in a service setting. n ¼ 1072 patients; n ¼ 652 patients with at least two ratings HoNOS65þ Inter-rater reliability Sensitivity to change Acceptability…”
Section: Inter-rater Reliabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…To measure severity, and ultimately outcome, Health of the Nation Outcome Scale (HoNOS) (Wing et al, 1996) and its variant HoNOS for elderly people (HoNOS65+) (Allen et al, 1999;Burns et al, 1999) were selected because they form part of the mental health minimum data-set and are consequently recommended in the National Service Framework (Department of Health, 1999).…”
Section: Methodsmentioning
confidence: 99%